2011
DOI: 10.4067/s0718-52862011000200004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of size on cost behaviour associated with tactical and operational flexibility

Abstract: Resumen Este trabajo realiza un análisis empírico sobre la influencia del tamaño en el comportamiento de los costes ante las dos situaciones típicas de flexibilidad operativa y táctica, mediante una muestra de explotaciones agrícolas. Los resultados indican que las explotaciones pequeñas presentan ventaja comparativa en las situaciones de flexibilidad operativa y táctica. El incremento de los costes indirectos ocasionado por la diversificación de productos aumenta con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
3
0
5
Order By: Relevance
“…In this respect, some prior studies found empirical evidence on the inability of managers to adjust resources, as well as on the incidence of objective factors and firm characteristics on cost stickiness (e.g. Anderson et al, 2003;Calleja et al, 2006;Argilés-Bosch and García-Blandón, 2011;Dalla and Perego, 2014;Balakrisnan et al, 2014). On the other hand, other studies stress on the deliberate decisions of managers, depending on expectations (Cooper and Kaplan, 1992;Yasukata and Kawijara, 2011;, past sales growth (Anderson et al, 2013), the type of adjusted resources (Balakrishnan and Gruca, 2008), manager's building incentives (Chen et al, 2012), CEO compensation and expectations for value creation of input resource expenditures (Banker et al,.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, some prior studies found empirical evidence on the inability of managers to adjust resources, as well as on the incidence of objective factors and firm characteristics on cost stickiness (e.g. Anderson et al, 2003;Calleja et al, 2006;Argilés-Bosch and García-Blandón, 2011;Dalla and Perego, 2014;Balakrisnan et al, 2014). On the other hand, other studies stress on the deliberate decisions of managers, depending on expectations (Cooper and Kaplan, 1992;Yasukata and Kawijara, 2011;, past sales growth (Anderson et al, 2013), the type of adjusted resources (Balakrishnan and Gruca, 2008), manager's building incentives (Chen et al, 2012), CEO compensation and expectations for value creation of input resource expenditures (Banker et al,.…”
Section: Introductionmentioning
confidence: 99%
“…Empresas maiores apresentam maior dificuldade em reduzir seus recursos em decorrência de diminuição das atividades pois são organizações complexas, com ampla gama de controle e transações e apresentam mais problemas de agência (Sepasi & Hassani, 2015). Por sua vez, nas empresas menores a decisão de ajustar os custos acontece de forma rápida, "[...] visto que a sua atividade se baseia essencialmente em recursos variáveis" (Sepasi & Hassani, 2015, p. 4146) e essas empresas são mais flexíveis tática e operacionalmente (Bosch & Blandón, 2011). o CPV aumentou em 0,88% para as grandes empresas e 0,96% para as pequenas e médias empresas, enquanto que nas diminuições de 1% da receita, o CPV diminuiu em 0,81% nas grandes empresas e 0,90% nas pequenas e médias.…”
Section: Fundamentação Teórica E Desenvolvimento Da Hipóteseunclassified
“…Com isso, este resultado não corrobora com estudos anteriores (ex. : Bosch & Blandón, 2011;Richartz & Borgert, 2020), de que empresas maiores apresentam maior assimetria nos custos, pois como já mencionado, o resultado não se mostrou significante estatisticamente. Este resultado pode ter sido encontrado devido a semelhanças que existem entre as empresas deste setor tal como: exercem suas atividades por meio de concessão dada pela União e sem concorrência (Costa & Castro, 2020) e também por serem empresas que podem ser consideradas de grande porte pelo fato de negociar suas ações na bolsa de valores.…”
Section: Análise Geralunclassified
“…The different authors lean towards different approaches for determining wage costs that are used to value unpaid labor. Here, one can consider both the employment relationship in agriculture [4] and outside agriculture [10,11] or the workplace in the same region [6,12] or not. Wage costs value the amount of unpaid labor, which in the FADN system is monitored by the indicator of the input of unpaid labor (FWU).…”
Section: Opportunity Costsmentioning
confidence: 99%